2018
DOI: 10.1111/cmi.12851
|View full text |Cite
|
Sign up to set email alerts
|

EhRho1 regulates phagocytosis by modulating actin dynamics through EhFormin1 and EhProfilin1 inEntamoeba histolytica

Abstract: The protist parasite Entamoeba histolytica causes amoebiasis, a major public health problem in developing countries and a major cause of morbidity and mortality. Invasive infection in amoebiasis mostly affects intestinal epithelial cell lining but can also involve other organs, such as liver, lungs, or brain. Phagocytosis is an essential mode of nutrition in amoeba and has often been associated with virulence behaviour of E. histolytica. E. histolytica possesses a highly dynamic and actin-rich cytoskeleton tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 76 publications
(126 reference statements)
4
35
0
Order By: Relevance
“…Both the mRNA and protein levels were reduced. Because both proteins have been shown to modulate actin dynamics it is not surprising that reduction in their levels led to reduced phagocytosis (54,55). How EhRrp6 specifically targets selected genes is intriguing and needs to be further investigated.…”
Section: Exonuclease Ehrrp6 In Growth Stressmentioning
confidence: 99%
“…Both the mRNA and protein levels were reduced. Because both proteins have been shown to modulate actin dynamics it is not surprising that reduction in their levels led to reduced phagocytosis (54,55). How EhRrp6 specifically targets selected genes is intriguing and needs to be further investigated.…”
Section: Exonuclease Ehrrp6 In Growth Stressmentioning
confidence: 99%
“…Subsequently, EhC2PK, a C2‐domain‐containing protein kinase gets enriched at the site. EhC2PK recruits EhCaBP1 to the membrane and initiates phagocytic cup formation through further recruitment of other molecules such as EhAK1, EhARPC1, EhARPC2, and EhRho1 (Babuta, Kumar, Gourinath, Bhattacharya, & Bhattacharya, ; Babuta, Mansuri, Bhattacharya, & Bhattacharya, ; Bharadwaj, Sharma, Janhawi Arya, Bhattacharya, & Bhattacharya, ; Jain et al, ; Mansuri et al, ; Somlata, & S., & Bhattacharya, A., ). During the progression of phagocytic cups to phagosomes, other molecules, such as EhCaBP3, EhCaBP5, and myosin1B become part of the complex participating in pseudopod fusion and phagosome separation from the membrane (Aslam et al, ; Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, we have observed that EhC2B localises at the phagocytic cup and pseudopods and is involved in erythrophagocytosis by the amoeba. However, the assembly of the actin monomer is essential for successful completion of the pseudopod formation as well as phagocytosis [10,38,39]. Several amoebic calcium-binding proteins are known to be involved in actin dynamics at the phagocytic cup [23,40].…”
Section: Ehc2b Is An Actin Nucleatormentioning
confidence: 99%
“…Many actin regulatory/binding proteins govern the constant turnover of the actin filament [51]. In E. histolytica, several actin-binding proteins (ABPs) for example, EhFormin1, EhCaBP1, EhCaBP3, EhCoactosin, and EhNCABP116 have already been characterized and are shown to be involved in phagocytosis [10,12,23,27,52,53]. Ca 2+ is another prominent regulator of the actin cytoskeleton in E. histolytica [54,55].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation